2018
DOI: 10.5603/imh.2018.0031
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on physical health threatening factors of Iranian seafarers working on ocean going tankers

Abstract: Background: Seafaring is a highly physically demanding profession in a risky environment due to exposure to unique job health related risk factors. The purpose of the study is to describe physical health threatening factors of Iranian seafarers working on tankers. Materials and methods: A qualitative content analysis with inductive approach was performed on 17 Iranian male seafarers in 2016. Subjects were selected by purposive sampling, which continued until data saturation. Data were gathered using semi-struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In terms of study design, the majority of the studies (12) were cross-sectional [ 10 , 27 30 , 32 , 34 , 36 , 40 , 44 , 45 , 48 ], whereas 3 of them were designed as qualitative [ 39 , 43 , 47 ], three studies as pre-and post/interventional [ 8 , 38 , 42 ], one reported retrospective design with existing data [ 46 ] and 7 studies did not report the study design [ 6 , 26 , 31 , 33 , 35 , 37 , 41 ]. At least two studies applied mixed methodology which probably was presented in separate articles [ 8 , 38 – 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In terms of study design, the majority of the studies (12) were cross-sectional [ 10 , 27 30 , 32 , 34 , 36 , 40 , 44 , 45 , 48 ], whereas 3 of them were designed as qualitative [ 39 , 43 , 47 ], three studies as pre-and post/interventional [ 8 , 38 , 42 ], one reported retrospective design with existing data [ 46 ] and 7 studies did not report the study design [ 6 , 26 , 31 , 33 , 35 , 37 , 41 ]. At least two studies applied mixed methodology which probably was presented in separate articles [ 8 , 38 – 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…There have been very few studies of assessing the relationship between diet and non-communicable diseases at sea [3,39,40]. In such studies, only one or two tools has been used to evaluate the dietary intake of the participants [39].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations